Proper dietary crude protein and metabolizable energy levels on growth performance, carcass characteristics and meat quality of Royal Project Bresse capon - Ongart Songsee (2020)
Copyright © 2020. The optimum crude protein (CP) and metabolizable energy (ME) levels were determined in a Bresse capon diet. In each trial, 120 Bresse cockerels aged 4 wk were castrated using the laparoscopic vacuum testectomy technique and allotted to four dietary groups according to a 2 × 2 factorial complete randomized design. Trial 1 (age 5–10 wk) consisting of a high CP diet (21%) promoted significantly higher final body weight (FBW), body weight gain (BWG), average daily gain (ADG), CP and ME intake with a better feed conversion ratio (FCR) than a low CP diet (19%), while a high ME diet (3.3 kcal ME/g) resulted in significantly lower feed intake (FI) and CP intake but promoted better FCR than a low ME diet (3.0 kcal ME/g). There was no interaction between the CP and ME levels for all parameters (p > 0.05). Trial 2 (age 11–13 wk) resulted in the high CP diet (19%) promoting significantly (p < 0.05) better FBW, BWG, FCR, ADG, CP intake, percentage of carcass, breast, thigh, liver, drumstick and breast moisture content than the low CP diet (17%). In contrast, the low ME diet (3.0 kcal/g) significantly (p < 0.05) provided higher FI, FBW, thigh moisture and fat, BWG, ADG, CP intake, breast moisture content and fat but lower abdominal fat, thigh meat and breast shear force than the high ME diet (3.3 kcal/g). There were interactions between the main factors on FI, FCR, ME intake and thigh meat. In conclusion, the optimum diet for Bresse capon aged 5–10 wk should contain 21% CP with 3.3 kcal ME/g and for age 11–13 wk should contain 19% CP with 3.0 kcal ME/g to achieve the best performance of the tested parameters.